Dinamika kemiskinan pedesaan di Kalimantan Barat: Analisis data panel - Supriaman Supriaman (Journal of Economics Research and Policy Studies, 2026)
Rural poverty remains an urgent challenge in many parts of Indonesia, including West Kalimantan. Despite ongoing poverty reduction efforts, a persistent gap remains between urban and rural areas. This study examines the dynamics of rural poverty in West Kalimantan using panel data analysis. By analyzing longitudinal data over time, we assess the factors associated with rural poverty and identify key trends and patterns. The panel-data approach accounts for both individual and time effects, allowing a more comprehensive understanding of poverty dynamics in the region. The results indicate that, in partial estimations, education level and GDP are negatively associated with poverty. The findings also show that education, open unemployment, and GDP jointly have a statistically significant effect on rural poverty rates. These results suggest that improving education quality, expanding employment opportunities, and strengthening household economic well-being are strategic priorities for reducing rural poverty.